Peningkatan Keselamatan Kerja Melalui Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) - Annisa Dwi Febriyanti; Dwi Titis Rahmania R; Rizya Dwi Yulinar; Satria Fajar Samudra; Denny Oktavina Radianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: In the modern industrial era, work safety is the main focus of companies to protect workers and minimize the risk of work-related injuries and illnesses. Implementation of an Occupational Safety and Health Management System (SMK3) has become a strategy adopted by many companies to improve safety and health standards in the workplace. The purpose of this writing is to provide a better understanding of the importance of implementing SMK3 in improving occupational safety and health as well as the factors that influence its success. Method: The research method used is a literature review which is an approach that focuses on collecting, evaluating and synthesizing information from various literature sources related to the research topic. In the case of journals that consider improving occupational safety through the implementation of an Occupational Safety and Health Management System (SMK3) Result: Work safety, including the implementation of the Occupational Safety and Health Management System (SMK3), is a shared responsibility of the company and workers' rights to a safe work environment. SMK3 aims to prevent occupational injuries and illnesses with steps such as risk identification and follow-up evaluation. Despite benefits such as increased productivity, implementation is often hampered by a lack of awareness, resources and resistance to change. Overcoming these barriers requires increased awareness, adequate resource allocation, and effective change management. Work safety and the implementation of SMK3 are the keys to creating a safe and productive work environment, requiring commitment and participation from all parties to succeed.